Quantifying the burden of Rift Valley fever in humans using disability adjusted life years, Kenya - Orinde, A.B. (Jomo Kenyatta University of Agriculture and Technology, 2013)
Rift Valley Fever (RVF) virus causes severe epidemics in livestock and humans resulting in considerable economic losses from disruption of livestock production, market chain and morbidity and mortality in humans. Public and private sector costs were incurred through service delivery for prevention and control. At the public health sector, RVF epidemic resulted in severe public health consequences of high morbidity and mortality (a total of 684 human cases with 155 deaths in Kenya). The losses are primarily incurred by households in terms of lost income due to illness, loss of human life and household’s expenditures in caring for the patients. This study estimated the burden of disease due to RVF in humans using Disability adjusted life years (DALYs), assessed human health RVF epidemiological parameters and private and public health costs during the last RVF epidemic in the 2006/2007 in Kenya. Family members who cared for an infected person in an eligible household and key informant in the public health sector in Garissa, Baringo and Kilifi districts and public health leaders at the national level were interviewed to aid in estimation of the private and public health costs. An eligible household was a household that had an RVF cases during the 2006/2007 outbreak as identified from the line list. Secondary data from the Ministry of Health and published literature were reviewed for epidemiological parameters including age and sex categorized incidences and mortality rates in order to compute DALYs using methods developed by the World Health Organization and World Bank. A total of 127 eligible households were enrolled into the study and one member interviewed in each household. Those interviewed in these households included 54% males and their xvii ages ranged from 19 to 81 years old with 40 and 45 years as mode and median age, respectively. The RVF virus predominantly infected males during the outbreak with a crude incidence of 0.7 per 1,000 population compared to females at 0.5 per 1,000 population. Total DALYs lost during the 2006/2007 outbreak was 4,035 (3.4 DALYs per 1000 population) for the reported cases of human RVF, representing 0.7% of the total DALYs for Kenya and estimated household costs of USD 120 for every human case reported. In comparison, HIV/AIDS and malaria are the leading causes of DALYs in Kenya at 24.2% and 7.2% of the total DALYs respectively. Rift Valley Fever is a zoonotic disease and it causes a considerable number of person DALYs yet it has not been considered prioritized by the policy makers’ in terms of resource allocation for prevention and control. Results from this study provide vital data on burden of RVF for use by the Government and other institutions to guide in health policy making and resource allocations for prevention and control of RVF to prevent future outbreak in Eastern Africa region.